Clinical experiences of Unimas nursing students - Noorul Izzah, Binti Ibrahim (Universiti Malaysia Sarawak (UNIMAS), 2013)
The purpose of this study was to explore the clinical experiences of nursing students, particularly the second, third and fourth year of UNIMAS nursing students. Overall, there were twelve participants involved in this study. The researcher used qualitative approach with purposive sampling to explore the perspectives and views of local population on their clinical practices. The obtained data were manually analyzed based on the research questions and the research objectives. The emerged themes acquired from the interview includes the beginning clinical exposure in Clinical Skills Developments Laboratory (CSDL), initial experiences in clinical areas which touched on the mixture of feeling, later experiences in clinical areas which highlighting the feeling of 'gradually improving' in clinical performances, inter-relationship between nursing students and staffs, clinical teachers, colleagues and patients, and last but not least was the existence of theory practice gap in the clinical areas. From the findings, it is hoped to improve and enhance the learning and teaching system of nursing education, in the future.